The Impact of Employees’ Recognition, Rewards and Job Stress on Job Performance - Syed Durrab Hussain; Dr. Abdul Khaliq; Qasim Ali Nisar; Aamir Zamir Kamboh; Shahzad Ali (SEISENSE Journal of Management, 2019)
Aim - the purpose of this study is to examine the role of employee rewards, recognition, and job-related stress towards employee performance considering the mediating role of perceived organizational support in the call-centers located in Lahore, Pakistan.